2016
DOI: 10.1589/jpts.28.945
|View full text |Cite
|
Sign up to set email alerts
|

Effect of core muscle thickness and static or dynamic balance on prone bridge exercise with sling by shoulder joint angle in healthy adults

Abstract: [Purpose] To date, core muscle activity detected using ultrasonography during prone bridge exercises has not been reported. Here we investigated the effects of core muscle thickness and balance on sling exercise efficacy by shoulder joint angle in healthy individuals. [Subjects and Methods] Forty-three healthy university students were enrolled in this study. Ultrasonography thickness of external oblique, internal oblique, and transversus abdominis during sling workouts was investigated. Muscle thickness was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Park et al investigated the effects of stabilization exercises performed in different shoulder joint ranges of motion on static and dynamic balance in healthy adults. There was no difference in balance between the exercises performed at different shoulder angles (33).…”
Section: Discussionmentioning
confidence: 75%
“…Park et al investigated the effects of stabilization exercises performed in different shoulder joint ranges of motion on static and dynamic balance in healthy adults. There was no difference in balance between the exercises performed at different shoulder angles (33).…”
Section: Discussionmentioning
confidence: 75%
“…In studies conducted on different musculoskeletal diseases that cause widespread chronic pain such as low back pain, knee osteoarthritis, and fibromyalgia, it has been observed that as the severity of pain increases, the balance ability deteriorates, postural stability oscillations increase, and risk of falling and fear of falling increase (31,32). However, the number of studies looking at this relationship was limited in shoulder pain.…”
Section: Table 2 Spadi Five Times Sit To Stand and Balance Test Score...mentioning
confidence: 99%
“…The authors note that after 10 weeks' course indicators of heart beats rate improved (135.4-124.2 bpm) as well as breathing coefficient (1.1-0.9). Pilates practicing weakens stress, anxiety, fatigue and improves students' self-feeling and motivation [15,21,26,27]. Theoretical principles of motivation's formation for callanetics practicing by students are regarded in other works [5,8].…”
mentioning
confidence: 99%